Aerobic and facultative microorganisms isolated from corroded metallic structures in a hydroeletric power unit in the amazon region of Brazil - Correia, Amabel Fernandes (2010)
Aerobic and facultative bacteria belonging to the Enterobacteriaceae, Pseudomonadaceae, Bacillaceae, Corynebacteriaceae and Streptococcaceae families have been isolated from corroded metallic structures of a hydroelectric power unit in the Amazon region of Brazil. In addition to anamorphic dematiaceous and moniliaceous fungi, members of the archeobacteria kingdom were also detected in the same samples. Scanning electron micrographs of metal bars cultivated with consortia of the isolated microorganisms depicted suggestive images of biofilm formation and corroded metallic structures questioning the possible role of these microorganisms in the corrosion activity. We also found Amazonian medicinal plants exhibiting inhibitory activity against some of the isolated microorganisms. Our new findings need additional studies to confirm the participation of some isolated microorganisms in the process of metallic degradation despite our main question if are there particular microorganisms involved in the corrosion process? or if physicochemical conditions would favor the development of a particular microbiota and consequently the corrosion process would result from its metabolism? Therefore we hypothesize that any microorganism could be potentially involved in the genesis of corrosion process. This is the first report in the literature dealing with microbiologically induced corrosion in the Amazon region which is especially characterized by its high humidity and elevated temperature all year round.